Experimental Solution of Chitosan and Nanochitosan on Wettability in Root Dentine: In Vitro Model Prior Regenerative Endodontics - Arias Alvarado, Fernando; Iriarte, Maira Rivero; Jordan Mariño, Freddy; Quijano-Guauque, Sara; Pérez, León D.; Baena, Yolima; García-Guerrero, Claudia (International Journal of Biomaterials, 2021)
Context. The wettability of the chemically modified dentin substrate is a condition that intervenes in dentin-vascular and cellular interaction across regenerative endodontics. Aims. To compare the effect of CS and CSnp on the wettability in root dentine with other irrigation protocols with an experimental in vitro model prior regenerative endodontics. Methods and Material. An in vitro experimental study that included eighty hemisected human root distributed into 8 groups: G1- distilled water; G2- 1% NaOCl/17% EDTA; G3- hypochlorous acid 0.025% HOCl, G4- 1% NaOCl/0.025% HOCl/17% EDTA, G5- 0.2 g/100 mL CS, G6- 1% NaOCl/0.2 g/100 mL CS, G7- CSnp, and G8- 1% NaOCl/CSnp. The wettability analysis calculated the contact angle (θ) between a drop of a blood-like and root dentinal surface; topographic characterization with scanning electron microscopy (SEM) quantified the diameter and number of tubules per area; spectroscopy infrared analyses (IR-S) identified chemical changes in the inorganic (phosphate/carbonate) and organic phase (amide/methyl). Statistical analysis: a linear mixed model, Kruskal–Wallis, and Holm–Bonferroni correction (P < 0.05) were used. Results. Significantly higher wettability for G2 (27.1 (P = 0.0001)) was found. A mean value of 67°±°for experimental groups (P = 0.07) was found, and we did not identify differences between them. The SEM identified greater tubular opening and erosion for G4 and greater dentinal permeability per area for NaOCl/CS. IR-S identified dentinal organic integrity with NaOCl-CS/CSnp compared to organic reduction promoted for NaOCl/EDTA. Conclusions. This in vitro dentin determined an indirect association between the wettability and organic contents. The oxidative effect of NaOCl could be neutralized by CS-CSnp, and consequently, the wettability of the substrate decreases.